The Self-Esteem of Dayak Ethnic Adolescents Reviewed from the Attachment Relationship of Parents - Grenadi, Kezia Margaretha; Mardi Rahayu, Maria Nugraheni (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Self-esteem is an assessment of oneself in terms of positive and negative things. Self-esteem can also be influenced by attachment with parents, namely mother and father. The purpose of this study was to determine whether there is a significant relationship between parental attachment, namely mothers and fathers with late adolescents. This study uses quantitative methods with scales as the measuring instrument used. The first scale is the Armsden and Greenberg Inventory of Parent and Peer Attachment with an α value = 0.898 on maternal attachment and an α value = 0.931 on paternal attachment. The second scale is the Rosenberg Self Esteem Scale (RSES) with a value of α = 0.795. The results of this study indicate that there is a significant relationship between maternal attachment and late adolescent self-esteem, namely p = 0.000 (p < 0.05) with a correlation value (r) of 0.322 and also on paternal attachment with late adolescent self-esteem, namely p = 0.000 (p < 0.05) with a correlation value (r) of 0.380. The relationship between these variables has positive results, meaning that the higher the attachment with parents, the higher the self-esteem in late adolescents. The implication of this study can be used as a reference in changing the output of parenting in parents, especially father role attachment on self-esteem of late adolescents.Harga diri merupakan penilaian pada diri sendiri terkait hal positif maupun negatif. Harga diri juga dapat dipengaruhi oleh kelekatan dengan orangtua yaitu ibu dan ayah. Tujuan penelitian ini adalah untuk untuk mengetahui apakah terdapat hubungan yang signifikan antara kelekatan orangtua yaitu ibu dan ayah dengan remaja akhir. Penelitian ini menggunakan metode kuantitatif dengan skala sebagai alat ukur yang digunakan. Skala pertama adalah Inventory of Parent and Peer Attachment Armsden dan Greenberg dengan nilai α = 0,898 pada kelekatan ibu dan nilai α = 0,931 pada kelekatan ayah. Skala kedua adalah Rosenberg Self Esteem Scale (RSES) dengan nilai α = 0,795. Hasil pada penelitian ini menunjukkan bahwa terdapat hubungan signifikan antara kelekatan ibu dengan harga diri remaja akhir yaitu p = 0,000 (p < 0,05) dengan nilai korelasi (r) sebesar 0,322 dan juga pada kelekatan ayah dengan harga diri remaja akhir yakni p = 0,000 (p < 0,05) dengan nilai korelasi (r) sebesar 0,380. Hubungan antar variabel ini memiliki hasil yang positif, artinya semakin tinggi kelekatan dengan orangtua maka semakin tinggi pula harga diri pada remaja akhir. Implikasi dari penelitian ini dapat digunakan sebagai referensi dalam mengubah output dari parenting pada orang tua khususnya kelekatan peran ayah pada harga diri remaja akhir.